Reaktivasi Pembelajaran Mulok Diniyah Dalam Meningkatkan Pemahaman Keagamaan Siswa Di SMP Negeri 2 Kabuh - Hidayat, Peni Nur; Umardiyah, Fitri; Chotimah, Chusnul (JoEMS (Journal of Education and Management Studies), 2025)
This study aims to determine the level of religious understanding of students in mulok diniyah learning. This research uses a quantitative approach method. The type of research used by researchers is pre-experimental research which is carried out using only one class without a comparison class. The subject of this research was class VIII C SMP Negeri 2 Kabuh Jombang. The research instruments used were pretest and posttest and questionnaire results as supporting data. The instrument is a test given twice (pretest and posttest) which contains statements to measure students' religious understanding in learning mulok diniyah before and after learning with flash card media. In addition to the test, there is a questionnaire instrument as supporting data on students' religious understanding. The data analysis technique used is hypothesis testing. However, before testing the hypothesis, the data obtained was first tested for normality. Based on the calculation of the paired sample t test, it shows that the significance value is 0.000. The significance value shows 0.000 < the error rate of 0.05 so it can be concluded that Ha is accepted. Acceptance of Ha means that there is an effect of students' religious understanding with flash card media on mulok diniyah learning.